ANALISIS TENGGANG CACAT PADA STRUKTUR BADAN PESAWAT MENGALAMI PERBAIKAN YANG DIOPERASIKAN OLEH TNI AU STUDI KASUS : BOEING 737-200, REG: AI-7301 - Rafif, Raihan
A crack defect is one of the common sources of failure in aircraft structures, which is no exception to components on aircraft that have repaired due to corrosion. The repaired is done so that the age of the structure increases so that the corrosion component can operate longer than it should. Repair can also save economy compared to buying new components. Although in terms of strength, structures that undergo improvements are not better with new components. Therefore, the determination of the age of a structure is very important when the sturcture is undergoing improvement. On this final project, damage tolerance analysis will be conducted on the structure of the aircraft that is undergoing repair operated by Air Force Military with the case study of Boeing 737-200. The structure that underwent the repair a keel beam lower chord that is located in the central part of the fuselage. Such improvements were made due to the corrosion occurring in the keel beam lower chord structure, so that the corrosion-affected part was replaced, but the structure must be remained able to withstand the load received. The static strength analysis is performed to determine how much load is received in the axial direction by the keel beam lower chord structure that has undergone improvement and is subsequently carried out a damage tolerance analysis of the keel beam lower chord structure that has undergone improvement. The static strength analysis is done by modeled the load retaining components in the centre of the fuselage, then simulated using the MSC PATRAN/NASTRAN software and obtained the result of the stress occurring in the axial direction of the keel beam lower chord component. After obtaining the axial stress that occurs, then a keel beam lower chord structure that has undergone improvement is modeled and simulated using the ABAQUS software to obtain a ? factor value at a specific crack length. The earned value is then processed with the flight mission profile data that occurs for the damage tolerance analysis by using the MATLAB software. Therefore, the load spectrum, operable lifetime and inspection interval on the keel beam lower chord structure has repaired.